When will smart antennas be ready for the market? Part II - results. - Kaiser, T.
The aim of this two-part forum is to shed more light on the future of smart antennas (SA) through discussions among a balanced group of experts from academia and industry. In part I, which appeared in the March 2005 issue of IEEE Signal Processing Magazine, each of the experts stated his own opinion after exchanging some thoughts by e-mail. Then, a panel session took place at ICAS-SP'05 and a public poll followed. Now, in part II, the results are summarized by the experts. The central topic of the forum was the expected market breakthrough of SA.
Keywords: Market breakthrough; Smart antennas